Self-directed learning of preclinical medical students in Basic Surgical Skills through remote teaching - Aleta, Karlos Noel R.
Background: Due to the COVID-19 pandemic, face-to-face teaching in medical schools was stopped and was forced to go online. Preclinical year levels were not allowed to have patient encounters. The surgical skills which would have been taught face-to-face during clinics were suspended. Hence the need to give students opportunities to engage in Self-Directed Learning (SDL). SDL is a core construct of adult learning from which students can describe and be understood as they journey through medical education.